Museums, History and Culture in Malaysia, Abu Talib Ahmad. Singapore: National University of Singapore Press, 2014, viii + 328 pp - Kevin Blackburn (Kajian Malaysia, 2015)
This book makes a valuable contribution to not just the debate about the representation of the past in Malaysia but to the broader area of scholarly research on museology in Asia. Abu Talib Ahmad's work on museums, history, and culture in Malaysia offers many insights into how present-day agendas have shaped the construction of the past in postcolonial societies.